The granulometry of the sediments of the sandy beaches of Santos (SP) - Ribeiro, Victor Vasques; Blanco, Ingryd Fernandes (Revista Sítio Novo, 2020)
Beaches are transitions between terrestrial and marine environments and primordial ecosystems influenced by several natural and anthropic factors. The transport and deposition of sediments on beaches is due to the processes that the near bodies of water suffered in the recent past. This study aimed to analyze the hydrodynamics of the bodies of water in the region of Santos (SP) by determining calcium carbonate content and sediment granulometry. The sediments of eight points were sampled and analyzed. The sediments had the prevailing diameter Very Thin (0.063 mm) and Thin (0.125 mm). No Gravel (2.0 mm) were found. The hydrodynamics of water bodies in the region is low, as has been previously proven in other studies. With the exception of Ponta da praia with similar results, the sediments of the other points presented higher calcium carbonate levels when compared to previous studies. The beaches of Santos still represent predominantly salicylic environments; however, the increase in calcium carbonate content may have provided a better environment for formations and gradual adaptations of certain species of organisms, which accompany such sediment changes. Keywords: Granulometry. Hydrodynamics. Sediment.